Sistem za sledenje igralcev v ¡sportnih igrah s pomocjo ra¡cunalniskega vida - Pers, J.; Kovacic, S. (Elektrotehnijski vestnik, 2000)
We present a computer vision system for tracking players in indoor team games, e.g. handball in our particular case. We describe several image processing and tracking methods, along with camera calibration and lens distortion correction. The output of the system consists of spatio-temporal trajectories of the players, which can be further processed and analyzed by sport experts. We present some experimental results as well.